No association of GABRA1 rs2279020 and GABRA6 rs3219151 polymorphisms with risk of epilepsy and antiepileptic drug responsiveness in Asian and Arabic populations: Evidence from a meta-analysis with trial sequential analysis - Zhang, Tiejun; Yang, Yi; Sima, Xiutian (Frontiers in Neurology, 2022)
γ-aminobuytric acid type A receptors (GABAAR) have been reported to contribute to the pathogenesis of epilepsy and recurrence of chronic seizures. Genetic polymorphisms in GABRA1 and GABRA6 may confer a high risk of epilepsy and multiple drug resistance, but with conflicting results. We aimed to assess the association of GABRA1 rs2279020 and GABRA6 rs3219151 with epilepsy risk using a meta-analysis. The databases of Pubmed, Ovid, Web of Science, and China National Knowledge Infrastructure were searched. Summary odds ratios (ORs) and 95% confidence intervals (CIs) were computed to evaluate the association between the polymorphisms and epilepsy risk using a fixed- or random-effect model. Trial sequential analysis (TSA) was performed to assess the results of meta-analysis. No significant association between the GABRA1 rs2279020 and GABRA6 rs3219151 and risk of epilepsy was found in Asian and Arabic populations. The negative results were also observed when comparing the GABRA1 rs2279020 and GABRA6 rs3219151 polymorphism to antiepileptic drug responsiveness. TSA confirmed the results of the meta-analysis. This meta-analysis suggests that GABRA1 rs2279020 and GABRA6 rs3219151 are not risk factors for the etiology of epilepsy and antiepileptic drug responsiveness in Asian and Arabic populations.